THE ECONOMICS OF WATER SUPPLY IN SRI AMAN, SARAWAK - Wong, Swee Kiong; K. Kuperan, Viswanathan; Khalid, Abdul Raham (2004)
Arising from the growing population and expanding economy, the increasing water demand in Malaysia has urged water supply authority throughout the country to improve their current water supply management and practices. In this study, 63 pooled data seta of the annual water production volume and costs for the nine water stations in Sri Aman were used to analyse the water delivery and production costs of the water supply authority in Sri Aman, Sarawak. Water supply function was derived from the marginal costs curve and from there, the supply elasticities were estimated. Based on the results of the multiple regression analysis, the Sri Aman Water Supply Authority (SAWSA) of Public Works Department is heavily subsidized by the government. The authority is incurring substantial losses from domestic and commercial water supply. However, it is enjoying a trivial economic rent for water supplied to industrial users. The supply elasticity of water production in Sri Aman showed that the expansion of water supply in Sri Aman is feasible. Thus, it is suggested that SAWSA should corporatise its water supply utilities to ensure a more efficient and effective management of the water supply to serve more people in the interior areas of Sri Aman.